If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6(5-3n)=5n+9
We move all terms to the left:
-6(5-3n)-(5n+9)=0
We add all the numbers together, and all the variables
-6(-3n+5)-(5n+9)=0
We multiply parentheses
18n-(5n+9)-30=0
We get rid of parentheses
18n-5n-9-30=0
We add all the numbers together, and all the variables
13n-39=0
We move all terms containing n to the left, all other terms to the right
13n=39
n=39/13
n=3
| -7.3-2.5x=5.2 | | -4+8t=28 | | 4(x-8)+3x=17 | | -8+3x=3 | | 3y+3=8y-6 | | 4(y-8)=32 | | 5r+8=-3r | | -7r+20=2r-4(1+3r) | | Y=16x-1-4x^2 | | -7r+20=2r-4(1+3r0 | | 18x^2=15x^2 | | 23=u/2-11 | | 4(2y-33)=28 | | x3−2x2−9x+18=0 | | 8.2x-2.1x=132 | | -9x-8=-6-2x | | 10=6+(0.4t) | | 560+x=1680 | | a/4-5=19 | | -9=9x+6x | | -4(-6x-3)=11 | | 12x-42=18 | | 16=10-4(5-5x) | | 1/3(x)+3/4=1 | | 4.2g+10=22g+22 | | 3(x-2)=-11 | | 5(9-2(6d-1))=11(4-10d)-139 | | -7+9x=-8x+8x | | 6x+8x+31=9x-15 | | 100=36+2(0.4s) | | 9/27p+9/27=-12 | | 3/4e-6=-2/5(e-10)-7 |